2019
DOI: 10.21873/invivo.11696
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogenicity of Parotid Gland Squamous Cell Carcinoma: A Study of 49 Patients

Abstract: Background/Aim: The aim of this study was to critically evaluate diagnostic workup, treatment and outcome of parotid gland squamous cell carcinoma (SCC). Patients and Methods: We retrospectively examined 844 consecutive cases of parotid surgery in a German teaching hospital between 1975 and 2017. Results: A total of 748 patients had parotid surgery. A total of 118 patients (15.7%) had a malignant tumour. Of those 49 patients had SCC accounting for 6.6% of all cases, and 41.5% of all malignant tumours. SCC typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 19 publications
2
24
0
2
Order By: Relevance
“…While all metastatic SCCs involved the parotid gland, primary SCCs affected both parotid and submandibular glands. The parotid gland is the most commonly involved major gland in primary SCC [1,3,14], although many isolated cases of submandibular gland origin have been reported [4,5,16,22,23]. The location of primary SCC as well as the age and sex of the patients were similar to those reported for salivary duct carcinomas.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…While all metastatic SCCs involved the parotid gland, primary SCCs affected both parotid and submandibular glands. The parotid gland is the most commonly involved major gland in primary SCC [1,3,14], although many isolated cases of submandibular gland origin have been reported [4,5,16,22,23]. The location of primary SCC as well as the age and sex of the patients were similar to those reported for salivary duct carcinomas.…”
Section: Discussionsupporting
confidence: 62%
“…SCC of the salivary gland is an uncommon occurrence, and most cases represent metastases from other head and neck sites [ 1 , 3 , 14 ]. There are few studies on primary SCC of the salivary gland [ 3 , 6 , 14 ], and a histologic comparison of primary and metastatic SCC has not been reported. The purpose of this study was to share helpful histologic features and diagnostic challenges between primary SCC and metastatic SCC of the salivary gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current case qualifies as SCC but showed unusual histological and clinical features leading to consideration of an alternative diagnosis: (1) the tumor presented at unusually young age (24 years in contrast to a mean age of 79 years for SCC of the parotid reported in the literature [4]; (2) it shows adnexal-type keratinization and variable other features reminiscent of adnexal-type differentiation; and (3) no other Clear cell aggregates mimicking mucoepidermoid carcinoma are evident focally. d CK19 immunostaining highlights abortive and wellformed rare ductal spaces primary tumor could be found by thorough clinical investigation.…”
Section: Discussionmentioning
confidence: 87%
“…It is reported that primary squamous cell carcinoma of parotid gland has no different characteristics relative to squamous cell carcinoma of other atomistic sites 10 . Still, evidence-based survival estimates of super cial and total parotidectomy for the symptomatic super cial parotid malignancy are lacking.…”
Section: Discussionmentioning
confidence: 99%